Existence and Continuous Dependence of the Solution of Non homogeneous Wave Equation in Periodic Sobolev Spaces - Santiago Ayala, Yolanda (2020)
In this article, we first prove that the initial value problem associated to the homogeneous wave equation in periodic Sobolev spaces has a global solution and the solution has continuous dependence with respect to the initial data, in [0; T], T > 0. We do this in an intuitive way using Fourier theory and in a fine version introducing families of strongly continuous operators, inspired by the works of Iorio [4] and Santiago and Rojas [7].Also, we prove that the energy associated to the wave equation is conservative in intervals [0; T], T > 0.As a final result, we prove that the initial value problem associated to the non homogeneous wave equation has a local solution and the solution has continuous dependence with respect to the initial data and the non homogeneous part of the problem.